Traffic separation, safety and ethics. - Zeitler, Ulli (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
For more than 25 years intensive efforts have been made to improve traffic safety. Yet, in defiance of extensive research it is not easy to discern the primary causes of these achievements. In fact, we have to consider several important factors, like traffic separation, traffic education programmes, technical improvements of car technology and traffic regulations. However, while each of these factors, separately and in combination, certainly have some positive effect within a relatively short time lapse, they tend, in the long run, to counteract our safety intentions. Furthermore, if we leave our current, most dominant interpretation of traffic safety in favour of a more appropriate, extended notion of traffic safety, even short-term improvements are highly questionable - or so I shall argue. Anyway, we have to deal with the fact that our fight against traffic fatalities and injuries has come to a dead end. It seems to be extremely difficult and costly to reduce our present traffic accident rate significantly. The falling accident rate pr. road-user has obviously levelled out. In what follows I want to propose a more appropriate notion of traffic safety which takes into account the ethical substance. Thereafter, the role of ethics in traffic safety discussions will be shortly illustrated. On this basis, the significance of traffic separation arrangements will be discussed and I shall argue that traffic separation will not promote but rather tend to prevent long-term improvements in traffic safety.